(untitled) (Vegueta: Anuario de la Facultad de Geografía e Historia, 2018)
El municipio de Santa Cruz de Tenerife surgió sin los recursos precisos para acometer las infraestructuras urbanas acordes con su rango de capital de la nueva provincia única de Canarias. Una circunstancia que debilitó su defensa de la capitalidad en un momento en el que, además, afloró otra disputa con el núcleo urbano-portuario de Las Palmas, la de la centralidad portuaria regional, insinuada desde finales de la década de 1840. La hacienda municipal santacrucera de la primera mitad del siglo xix debió nutrirse de arbitrios sobre el consumo, al carecer de una hacienda patrimonial, y estos arbitrios se vieron muy mermados por la difícil coyuntura económica del período. The municipality of Santa Cruz de Tenerife emerged without the resources necessary to negotiate urban infrastructure in an appropriate way to its status as capital of the newly unitary province of the Canaries. This situation weakened its claim to remain the capital at a time when another, further dispute with the urban-port hub of Las Palmas erupted, that of regional port centrality, which had been heating up from the late 1840s. During the first half of the nineteenth century, the municipal treasury of Santa Cruz de Tenerife had to subsist on consumption taxes, lacking municipal lands as it did, and these taxes were greatly diminished by the difficult economic circumstances of the period.